Country of birth and other factors associated with hepatitis B prevalence in a population with high levels of immigration. Issue 9 (22nd August 2013) - Reekie, Joanne; Gidding, Heather F.; Kaldor, John M.; Liu, Bette
Abstract: Background and Aim: While hepatitis B virus (HBV) prevalence is known to vary greatly between countries, systematically collected population‐level prevalence data from some countries is limited. Antenatal HBV screening programs in countries with substantial migrant populations provide the opportunity to systematically examine HBV prevalence in order to inform local and regional HBV estimates. Methods: A comprehensive register of Australian mothers giving birth from January 2000 to December 2008 was linked to a register of HBV notifications. Age‐standardized prevalence of chronic HBV were calculated overall and by the mother's country of birth. Multiple logistic regression was used to investigate other factors associated with HBV prevalence. Results: Five hundred twenty‐three thousand six hundred sixty‐five women were included and linked to 3861 HBV notifications. The age‐standardized HBV prevalence was low (0.75%, 95% confidence interval 0.72–0.79). The highest HBV prevalence rates were observed in women born in Cambodia (8.60%), Taiwan (8.10%), Vietnam (7.49%), China (6.80%), and Tonga (6.51%). Among Australia‐born women, those who smoked during pregnancy, were from a more disadvantaged socioeconomic background, and lived in remote areas were more likely to have HBV. There was also a trend suggesting a decrease in the prevalence of HBV over time. Conclusions: Antenatal screening for HBV can provide systematic population estimates of HBV prevalence in migrants and also identify other high prevalence groups. Longer follow‐up will be required to confirm the small decrease in HBV prevalence observed in this study.